Influência da taxa de infestação de Limnoperna fortunei no aumento da perda de carga em sistemas hidráulicos - Edwin Andres Mancilla Rico (2018)
The efficiency of a Francis turbine is related to the internal losses of the machine. These losses occur in the rotor in the distributor system, on spiral case and suction pipe. Suffering great influence of the design and the type of material used in manufacturing. In this case the variation of surface roughness can cause a significant impact on the performance of the turbines. Within this context the events of Bioincrustation fouling of Limnoperna fortunei, L. fortunei, popularly known as golden mussel, produce an increase in surface roughness, causing high head loss and reduced efficiency of the system. This paper presents the results of a search that allows estimating the influence of this Bioincrustation in hydraulic systems (adduction channel, spiral case and suction pipe in a small 15 to 200 metter Francis turbine, with a nominal flow varying from 7.38 m3/s to 0.58 m3/s, and 1000 kW power. The effect of biofouling on the turbine rotor has not been studied since the flow velocities inside the turbine rotor are higher than the pullout limit of 4.1 m/s. The determination of the head loss caused by the incrustation layers L.fortunei, it was initially calculated what maximum thickness of scale possible is, depending on the flow rate, so that L.fortunei, remains embedded. Then, it was calculated the head loss factor (f) for each section of the components studied, taking into consideration the presence or absence of incrustation of the mollusk. The absence of incrustation was limited to regions with flow speeds greater than 4.1 m/s. Based on the "f", it was given the increase in head loss, resulting from the number of incrustation layers. Some other expected results do not show that: i) incrustation of L.fortunei, causes the increased irregular flow rate of in both components studied; ii) incrustation also causes the reduction in the capacity of energy recovery in the suction pipe; iii) In a situation of L.fortunei, incrustation in five layers, there is head loss in spiral case and in the suction pipe the value is doubled in relation to head loss without incrustation; iv) increasing head loss due to incrustation in these components, shows the need for regular operations of L.fortunei, pest control in this turbine as well as indicates the importance of assessing the impact of the infestation throughout the plant's generation system.